PELATIHAN PENYUSUNAN INSTRUMEN LITERASI NUMERASI BERTEMA PERTANIAN BAGI GURU MI HIDAYATUL MUBTADI’IN SIDODADI TEMPUREJO - Safrida, Lela Nur; Sholekhah, Irmadatus; Setiawan, Toto Bara (Jurnal Pengabdian Masyarakat Khatulistiwa, 2024)
ABSTRACTAKMI as a comprehensive assessment is used to diagnose students' strengths and weaknesses in reading literacy, numeracy literacy, scientific literacy and socio-cultural literacy at MI, MTs and MA levels. MI Hidayatul Mubtadi'in Sidodadi Tempurejo is one of the schools that hold AKMI. AKMI results show quite satisfactory results. However, there needs to be improvement because there are still many students who are still at the basic level. One component that needs to be improved is strengthening facilitator capacity through training. Community service activities aim to overcome problems and fulfill the practical needs of MI Hidayatul Mubtadi'in Sidodadi Tempurejo through training and mentoring. Community service activities use a PAR approach. The activity stages consist of planning, training, mentoring and evaluation. The activity went smoothly. This activity provides additional knowledge for teachers regarding the concept of numeracy literacy and how to prepare numeracy literacy questions. The teachers have tried to arrange numeracy literacy questions according to their respective fields of study with the theme of agriculture.Keywords: AKMI, numeracy literacy, training, agricultureABSTRAKAKMI sebagai asesmen komprehensif digunakan untuk mendiagnosis kelebihan dan kelemahan peserta didik pada literasi membaca, literasi numerasi, literasi sains dan literasi sosial budaya pada jenjang MI, MTs, dan MA. MI Hidayatul Mubtadi’in Sidodadi Tempurejo sebagai salah satu sekolah yang melaksanakan AKMI. Hasil AKMI menunjukkan hasil yang cukup memuaskan. Namun perlu adanya peningkatan karena masih banyak siswa yang masih berada pada level dasar. Salah satu komponen yang perlu diperbaiki yaitu penguatan kapasistas fasilitator melalui pelatihan. Kegiatan pengabdian kepada masyarakat bertujuan untuk mengatasi masalah dan pemenuhan kebutuhan praktis MI Hidayatul Mubtadi’in Sidodadi Tempurejo melalui pelatihan dan pendampingan. Kegiatan pengabdian kepada masyarakat menggunakan pendekatan PAR. Tahapan kegiatannya terdiri dari perencanaan, pelatihan, pendampingan, dan evaluasi. Kegiatan berlangsung dengan lancar. Kegiatan ini memberikan pengetahuan tambahan bagi guru bidang studi mengenai konsep literasi numerasi serta bagaimana menyusun soal literasi numerasi. Guru-guru telah mencoba menyusun soal literasi numerasi sesuai dengan bidang studi masing-masing dengan tema pertanian.Kata Kunci: literasi numerasi, AKMI, pelatihan, pertanian